STRATEGI PENGEMBANGAN HASIL HUTAN BUKAN KAYU UNGGULAN DI KABUPATEN KAMPAR - RIAU - Suhesti, Eni; Hadinoto, Hadinoto; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
This study aims to 1) identify the types of NTFP and the level of excellence in Kampar District, 2) Formulate a potential HHBK development strategy to be excellent in Kampar District. The study was conducted on May -August 2016, with survey method. Data collection is done on three objects that are potential areas of NTFP, community and related offices. The data collection on the potential of NTFPs and the determination of the level of excellence of each type of HHBK shall be guided by the Minister of Forestry Regulation No.P.21 / Menhut-II / 2009. The results of the study identified the types of HHBK in Kampar Regency there are 9 types, namely: honey (from Apis dorsata), rattan (Calamus sp), durian (Durio zibethinus), mangosteen (Garcinia mangostana), tampui (Bacaurea macrocarpa) Scaphium macropodum), Pinang (Areca catechu), petai (Parkia speciosa) and gaharu (Aqularia malaccensis), with HHBK excellence class including class II and class III. D evelopment strategy of superior HHBK of Kampar Regency: 1) Improvem ent of product quality and diversification (honey and durian); 2) Increasing the quality of rural human resources; 3) Strengthening of rural institutions; 4) Facilities / business capital development, post-harvest handling and marketing.